PERANCANGAN SISTEM INFORMASI PENGELOLAAN DOKUMEN BERITA ACARA PEKERJAAN BERBASIS WEB - Yulianto, Dodi; Nur Hakim, Fitro; Solechan, Achmad (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2020)
PT. Data Utama Dinamika, is one of the providers of Internet service provider Internet Service Provider which was established in 2005. The company has a support and helpdesk division that prioritizes customer service. Some employees, especially the support division, had difficulties when looking for some document news events. In this case used information system news events. This information system aims to manage data news event, so more organized and in search data can be faster. The research methodology is carried out covering field study and literature study. Field studies include observations and interviews. While the literature study is done by library research relevant to the problem. This program uses waterfall modeling in system development. This report is useful for understanding ongoing system performance. Then it is depicted in Flow of Document. After the global draft is completed, it will be known to use the program. Usefulness is to assist the support division in performing its duties of data collection and search. As well as presentation of reports from Inventory, Customer Complaint to News Event Report, to be easy and fast without reducing the prevalence level.